Risk of adverse outcomes in Taiwan associated with concomitant use of clopidogrel and proton pump inhibitors in patients who received percutaneous coronary intervention - Huang, Chin-Chou; Chen, Yu-Chun; Leu, Hsin-Bang; Chen, Tzeng-Ji; Lin, Shing-Jong; Chan, Wan-Leong; Chen, Jaw-Wen (The American journal of cardiology, 2010)
Recent studies have suggested that proton pump inhibitors (PPIs) might reduce the inhibitory effect of clopidogrel on platelet aggregation, possibly through inhibition of the hepatic cytochrome P450 2C19 (CYP2C19) isoenzyme. The prevalence of CYP2C19 loss-of-function alleles is much greater among East Asians than among other populations. Thus, potential drug interactions might be more apparent. Therefore, we conducted a nationwide, population-based study using the Taiwan National Health Insurance database. We identified 3,278 patients (mean age 65.9 ± 11.9 years, 71.9% men) with coronary artery disease who had taken clopidogrel after percutaneous coronary intervention from the 1 million sampling cohort data set since January 1, 2002. Of the 3,278 patients, 572 had received concomitant PPIs for underlying gastrointestinal disease and 2,706 had not used PPIs. To the end of 2007, 1,410 patients had been rehospitalized, 970 patients had undergone revascularization, and 499 patients had died. According to the Kaplan-Meier analysis, the incidence of rehospitalization (p = 0.001) and mortality (p <0.001) was significantly greater for the patients with concomitant PPI use than for those without concomitant PPI use. However, the incidence of revascularization was similar in the 2 groups. Multivariate analyses showed that concomitant PPI use was associated with an increased risk of rehospitalization (hazard ratio 1.23, 95% confidence interval 1.07 to 1.41, p = 0.003) and mortality (hazard ratio 1.65, 95% confidence interval 1.35 to 2.01, p <0.001). In conclusion, the concomitant use of clopidogrel and PPIs should be done with care to avoid adverse outcome in East Asians patients who have undergone percutaneous coronary intervention.
Gesehen am 25.04.2023